Bibliometric Analysis: Exploring Research Trends in the Use of Google Sites in the Education Sector - Fransiska Romana Febrianti; Mohammad Masykuri; Endang Susilowati (Proceeding International Conference on Digital Education and Social Science, 2024)
Bibliometric analysis has become a powerful tool for mapping research concepts across various fields. However, the application of bibliometrics in education, particularly concerning the use of Google Sites, remains an untapped potential. This study aims to explore trends and research topics related to the utilization of Google Sites in education during the 2016–2024 period. Using the Dimensions database, we collected relevant publications and visualized them using VOSviewer. An in-depth analysis was conducted with a focus on bibliographic pairs of countries, institutions, journals, authors, and frequently used author keywords. From 495 publications that met the criteria, the findings revealed that Indonesia is the country with the most significant contribution to research on Google Sites in education. Additionally, the Jurnal Penelitian Pendidikan IPA emerged as the primary publication platform, Rogerson (2017) as the most-cited author, and Yogyakarta State University as the most productive institution. These findings indicate a growing interest in the use of Google Sites in education in Indonesia. However, further research is needed to delve deeper into the impact of using Google Sites on learning processes and student outcomes.